Management of sepsis in neutropenic patients: guidelines from the infectious diseases working party of the German Society of Hematology and Oncology - Penack, Olaf; Buchheidt, Dieter; Christopeit, M.; Lilienfeld-Toal, M. von; Massenkeil, G.; Hentrich, M.; Salwender, H.; Wolf, H.-H.; Ostermann, H. (Annals of oncology, 2011)
Sepsis is a leading cause of mortality in neutropenic cancer patients. Early initiation of effective causative therapy as well as intensive adjunctive therapy is mandatory to improve outcome. We give recommendations for the management of adults with neutropenia and sepsis. The guidelines are written for clinicians involved in care of cancer patients and focus on pathophysiology, diagnosis and treatment of sepsis during neutropenia.
Available online: 6 January 2020
Gesehen am 12.10.2022